The environmental public policy in Colombia: beyond the developmentalist paradigm (REVISTA NODO, 2017)
As it is conceived in Colombia and most countries of Latin America, the sustainable development has encouraged the deprotection of natural ecosystems. It is a corrective adaptation of market failures. It tries to hide the collateral effects of the market and the consumption. In the face of the  ruthless advance of the locomotive representing the development, alternatively, An important group of thinkers agree to rescue the thoughts of our indigenous ancestors and their respect for mother earth In a process of generation of alternatives applicable from the constitution of each country and your development plans, Including the valuation of their cultural individualities And the ecological system.